Traumatic dislocation of the testis - Mahapatra, Bibekananda; Deolekar, Sandesh; Singhal, Pragati; Khan, Nida; Kumar, Manish; Singh, Shashwat (International Surgery Journal, 2019)
Traumatic dislocation of testis is an uncommon condition and usually occurs after direct impact on the scrotum. The diagnosis may be overlooked because of associated major injuries or due to lack of awareness of its possible occurrence. We report a case of traumatic displacement of testis in a young man presented to the emergency following polytrauma. The patient underwent a successful surgical exploration without loss of testicular function. A high index of suspicion is therefore necessary to diagnose traumatic testicular displacement.